DETERMINATION OF CRITERIA AND INDICATORS FOR GOOD GOVERNANCE IN MANAGEMENT FOR THE SUSTAINABILITY OF THE FISHERY RESOURCES OF THE GULF OF NICOYA AND IN PARTICULAR OF THE COMMUNITIES OF COSTA DE PÁJAROS AND MANZANILLO - Pacheco-Urpí, Oscar (2013)
Defined criteria and indicators of sustainability of fishery resources, in the dimensions: social, economic, environmental and political and institutional, at a general level in the region of the Gulf of Nicoya and two communities of the inner part of the Gulf of Nicoya, Costa of birds and Manzanillo. Indicators of driving forces of pressure on fisheries are primarily established in demand, poverty, the need for exclusive income of fishing and the policy of subsidy or price preference of the fuel to fishermen. It is determined between the criteria of non-sustainability of coastal marine resources, poor governance, which encourages a poor governance, which emphasizes the enormous problem of planning and execution of the institutions. Is determined the need to integrate criteria and indicators of sustainability and good governance, the generation of new employment opportunities and production, as well as training.